Pulmonary embolism in patients with COVID-19: characteristics and outcomes in the Cardio-COVID Italy multicenter study - Ameri, Pietro; Inciardi, Riccardo M.; Di Pasquale, Mattia; Agostoni, Piergiuseppe; Bellasi, Antonio; Camporotondo, Rita; Canale, Claudia; Carubelli, Valentina; Carugo, Stefano; Catagnano, Francesco; Danzi, Giambattista; Dalla Vecchia, Laura; et al. (Clinical research in cardiology, 2021)
Background Pulmonary embolism (PE) has been described in coronavirus disease 2019 (COVID-19) critically ill patients, but the evidence from more heterogeneous cohorts is limited. Methods Data were retrospectively obtained from consecutive COVID-19 patients admitted to 13 Cardiology Units in Italy, from March 1st to April 9th, 2020, and followed until in-hospital death, discharge, or April 23rd, 2020. The association of baseline variables with computed tomography-confirmed PE was investigated by Cox hazards regression analysis. The relationship between d -dimer levels and PE incidence was evaluated using restricted cubic splines models. Results The study included 689 patients (67.3 ± 13.2 year-old, 69.4% males), of whom 43.6% were non-invasively ventilated and 15.8% invasively. 52 (7.5%) had PE over 15 (9–24) days of follow-up. Compared with those without PE, these subjects had younger age, higher BMI, less often heart failure and chronic kidney disease, more severe cardio-pulmonary involvement, and higher admission d -dimer [4344 (1099–15,118) vs. 818.5 (417–1460) ng/mL, p < 0.001]. They also received more frequently darunavir/ritonavir, tocilizumab and ventilation support. Furthermore, they faced more bleeding episodes requiring transfusion (15.6% vs. 5.1%, p < 0.001) and non-significantly higher in-hospital mortality (34.6% vs. 22.9%, p = 0.06). In multivariate regression, only d -dimer was associated with PE (HR 1.72, 95% CI 1.13–2.62; p = 0.01). The relation between d -dimer concentrations and PE incidence was linear, without inflection point. Only two subjects had a baseline d -dimer < 500 ng/mL. Conclusions PE occurs in a sizable proportion of hospitalized COVID-19 patients. The implications of bleeding events and the role of d -dimer in this population need to be clarified. Graphic abstract